CONTRIBUTION OF SUBSIDIES TO THE LEVEL OF INCOME OF SMALL FARMS IN BULGARIA - Nikolaj Stefanov (Journal of Bio-Based Marketing, 2020)
The article examines the relationship between subsidies paid and the profitability achieved on small agricultural holdings in Bulgaria. The regression analysis examines the relationship between subsidies as factorial values ​​and indicators – gross margin, net operating income and profitability of subsidies as outputs. It is determined what is the impact of the subsidies on the yield and what happens in case of a threshold increase in their size, regardless of the localization, intensification and specialization of the small farms. The results of the regression analysis show that subsidies lead to a threshold increase in farm incomes and increase the quality of products.